Gender Pay Gaps and the Restructuring of Graduate Labour Markets in Southern Europe. - Figueiredo, Hugo (2016)
In this paper we investigate whether education-job mismatches and growing occupational diversity are important explanatory factors of gender pay gaps among university graduates in Southern Europe (namely in Portugal, Spain, and Italy). In our analysis we use standard decomposition techniques and test the implications of controlling for selection bias. Our results indicate that overeducation and greater occupational segregation associated with the emergence of new graduate job profiles, are important determinants of earnings inequality. While our focus is on graduates’ early careers, demonstrating that occupational assignment and selection into employment shape gender pay gaps among the highly skilled provides a more pessimistic view on the ability of educational expansion or equal pay legislation to significantly reduce gender pay inequality. Southern European economies are also particularly interesting to look at since there may be a greater degree of mismatch between the pace of higher education expansion and the changes in the job structure, making women particularly vulnerable to overeducation.